Role of Religion in the Conservation of Environment: A Study of Environmental Ethics in Islam - Zargar, Nazir Ahmad (International Journal of Psychosocial Rehabilitation, 2019)
Conservation of the environment has been a subject of serious attention ever since the Industrial Revolution took place. With every passing day, its importance is felt more and more. Almost every aspect of this burning issue has been thoroughly discussed by experts and scholars worldwide. As a result, very fruitful and beneficial suggestions have come up, and so many essential resolutions have been passed so far. Nevertheless, a sincere implementation of these suggestions and resolutions has been missing so far at the individual, public, governmental and international levels. Religion, a very potent factor in shaping the minds and behavioural attitudes of almost the whole human population across the globe, can play a vital role in conserving the environment. Islam is the second largest religion in the world followed by nearly two billion people across the world constituting one-fourth of the whole human population. Islam teaches that the fundamental purpose of the existence of humans on this planet is to worship the Creator. That actually means striving for the attainment of good for themselves and for other beings. The basic objectives of the Sharī‘ah aim to establish a society where everybody gets his due and the collective interest is fulfilled even if at the cost of the individual interest. One of the foremost objectives of the Sharī‘ah is to preserve life. The Qur’ān states that harming a life is as if humanity has been harmed while saving a life amounts to saving the lives of the whole of humanity. It is further said that God has created this world on a balance. Anyone who disturbs this balance commits an offense. This shows that man has an essential responsibility toward the preservation of his environment. Islam guides towards a three-dimensional God—man— universe relationship. While on one hand man has been asked to worship his Creator, on the other hand worshipping the Creator is not only confined to fulfilling some set rituals but serving the creation and the environment. This paper highlights the teachings of Islam enshrined in its primary sources of the Qur'ān and Ḥadīth (traditions of the Prophet, peace be upon him) and the relevant literature regarding the conservation of the environment and environmental ethics. It explores how an individual Muslim can play a positive role in the conservation of the environment for the betterment of humanity at large, as every Muslim at individual and collective levels has a religious obligation to act according to the teachings of his religion.